Azithromycin Causes a Novel Proarrhythmic Syndrome. (April 2017) - Yang, Zhenjiang; Prinsen, Joseph K.; Bersell, Kevin R.; Shen, Wangzhen; Yermalitskaya, Liudmila; Sidorova, Tatiana; Luis, Paula B.; Hall, Lynn; Zhang, Wei; Du, Liping; Milne, Ginger; Tucker, Patrick; et al.
Abstract : Background—: The widely used macrolide antibiotic azithromycin increases risk of cardiovascular and sudden cardiac death, although the underlying mechanisms are unclear. Case reports, including the one we document here, demonstrate that azithromycin can cause rapid, polymorphic ventricular tachycardia in the absence of QT prolongation, indicating a novel proarrhythmic syndrome. We investigated the electrophysiological effects of azithromycin in vivo and in vitro using mice, cardiomyocytes, and human ion channels heterologously expressed in human embryonic kidney (HEK 293) and Chinese hamster ovary (CHO) cells. Methods and Results—: In conscious telemetered mice, acute intraperitoneal and oral administration of azithromycin caused effects consistent with multi-ion channel block, with significant sinus slowing and increased PR, QRS, QT, and QTc intervals, as seen with azithromycin overdose. Similarly, in HL-1 cardiomyocytes, the drug slowed sinus automaticity, reduced phase 0 upstroke slope, and prolonged action potential duration. Acute exposure to azithromycin reduced peak SCN5A currents in HEK cells (IC50 =110±3 μmol/L) and Na + current in mouse ventricular myocytes. However, with chronic (24 hour) exposure, azithromycin caused a ≈2-fold increase in both peak and late SCN5A currents, with findings confirmed for INa in cardiomyocytes. Mild block occurred for K + currents representing IKr (CHO cells expressing hERG; IC50 =219±21 μmol/L) and IKs (CHO cells expressing KCNQ1+KCNE1; IC50 =184±12 μmol/L), whereas azithromycin suppressed L-type Ca ++ currents (rabbit ventricular myocytes, IC50 =66.5±4 μmol/L) and IK1 (HEK cells expressing Kir2.1, IC50 =44±3 μmol/L). Conclusions—: Chronic exposure to azithromycin increases cardiac Na + current to promote intracellular Na + loading, providing a potential mechanistic basis for the novel form of proarrhythmia seen with this macrolide antibiotic. Abstract : Supplemental Digital Content is available in the text.